Implementation of tahfizhul Qur'an learning at PPTQ Griya Qur'an 3 Putri Klaten - Hastini Hastini; Maslamah Maslamah (UIN Raden Mas Said Surakarta, 2021)
The management of the PPTQ Griya Qur'an 3 Putri Klaten has been designed with modern management carried out by ustadzah (female teacher) and mudir as the center. The number of students was 80, and had graduated 2 generations of around 40 students. The purpose of this research is to describe the teaching and learning process at Tahfidz Qur'an. This research used a qualitative descriptive method, conducted at the PPTQ Griya Qur'an 3 Putri Klaten in January-July 2020. The research subjects were ustadzah. The informants were the boarding school leaders and the students. Data collection was carried out by observation technique, interviews, and documents. The validity of the data used source and data triangulation techniques. Meanwhile, the analysis technique used interactive data analysis encompassing data collection, data reduction, then presentation and conclusion. Based on the research, there are three stages of learning tahfizh; the first is the preliminary stage (pre-instructional), the second is the core stage (instructional) containing the implementation of muraja'ah and ziyadah students, then the teacher listens/justifies the students' readings, and the third is assessment stage. Evaluations include daily evaluations and level-up evaluations. Daily evaluation is done by the verse memorized every day, while the evaluation of the time level can be carried out at any time when the students are ready to memorize 30 juz’.